Response to low soil nitrogen stress of S1 maize breeding lines selected for high vertical rootpulling resistance - Kamara, A.Y.; Menkir, A.; Kureh, I.; Omoigui, L.O. (2006)
Poor soil fertility, especially with low levels of nitrogen (N), is a major constraint to productivity and the production of maize in the Guinea Savanna of Nigeria. To improve efficiency of the maize to use N in the Savanna, maize genotypes with improved root systems to exploit the available N from the soil and to give optimum yields even at low N levels are required. Vertical root-pulling resistance has been shown to relate well to the rooting characteristics of the maize plant and could be an important secondary trait for use in improving the efficiency of selection of maize genotypes for tolerance of low-N stress. This study assessed the performance under low-N conditions, of S1 maize breeding lines, selected for high vertical root-pulling resistance. Results of the evaluations showed that breeding lines having high vertical root-pulling resistance produced higher grain yields than those having low vertical root-pulling resistance, especially under severe and moderate N-stress, with exception of the prolific types. Some prolific maize breeding lines though, having low vertical root-pulling resistance, produced high grain yields that were comparable to the high-yielding breeding lines having high vertical root-pulling resistance. Grain yield under severe and moderate N-stress was associated with total dry matter, harvest index, leaf area index, stay-green rating, number of ears per plant and plant and ear heights. Negative associations between grain yield and anthesis-silking interval, .4;td days to silking were also observed' The good performance of the breeding lines having high vertical root-pulling resistance indicates that their root characteristics may have enabled them to exploit N from the soil even at a low N level to produce a high grain yield. Therefore, we conclude that the selection of maize genotypes for high vertical root-pulling resistance and prolificacy would also produce genotypes with tolerance to low-N stress.